Artificial Intelligence (AI) Adoption as Marketing Tools among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia - Allicia Deana Santosa; Iis Surgawati (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
Despite MSMEs' crucial role in Indonesia's economy, their utilization ofartificial intelligence (AI) remains restricted. This paper investigates theadoption of artificial intelligence (AI) among micro, small, and mediumenterprises (MSMEs) in Indonesia, providing a comprehensive analysis of thedifficulties and potential advantages. AI implementation is essential for thesebusinesses because it may significantly enhance economic growth throughimproved productivity, cost reduction, and increased competitiveness.Furthermore, AI facilitates the decision-making process and fosters data-basedinnovation. The study investigates the correlation between competitivepressure, top management commitment, staff adaptability, perceived utility,and simplicity of use in the adoption of artificial intelligence (AI) amongmicro, small, and medium enterprises (MSMEs) in Indonesia. By addressingthese gaps, we can enhance our comprehension of how MSMEs can utilize AIadoption as a marketing tool, thereby fostering their growth and success. Theresults emphasize the significance of top management commitment (TMC),employee adaptability (EA), perceived usefulness (PU), and perceived ease ofuse (PEOU) in encouraging the adoption of AI among micro, small, andmedium enterprises (MSMEs) in Indonesia.